2021
DOI: 10.1002/biof.1763
|View full text |Cite
|
Sign up to set email alerts
|

The cardioprotective effects of hydrogen sulfide by targeting endoplasmic reticulum stress and the Nrf2 signaling pathway: A review

Abstract: Cardiac diseases are emerging due to lifestyle, urbanization, and the accelerated aging process. Oxidative stress has been associated with cardiac injury progression through interference with antioxidant strategies and endoplasmic reticulum (ER) function. Hydrogen sulfide (H 2 S) is generated endogenously from L-cysteine in various tissues including heart tissue. Pharmacological evaluation of H 2 S has suggested a potential role for H 2 S against diabetic cardiomyopathy, ischemia/reperfusion injury, myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Once regarded as merely a toxic and foul-smelling gas, H 2 S has more recently been recognized as a key signaling molecule and important endogenous mediator of numerous physiological and pathophysiological processes within mammalian systems. Its positive influence on the cardiovascular system, in particular, is rooted in its involvement in vasodilation (activation of K ATP channels and the PI3K/Akt signaling pathway) [ 178 , 179 , 180 , 181 ], as well as its anti-inflammatory (inhibition of the p38 MAPK/NF-κB pathway) [ 182 , 183 ], antioxidative (activation of the Nrf2 signaling pathway) [ 59 , 168 , 184 ], and anti-apoptotic (suppression of pro-apoptotic genes Bid, Apaf-1, and p53) [ 140 ] properties, which have been extensively reviewed elsewhere in the literature [ 54 , 55 , 116 , 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once regarded as merely a toxic and foul-smelling gas, H 2 S has more recently been recognized as a key signaling molecule and important endogenous mediator of numerous physiological and pathophysiological processes within mammalian systems. Its positive influence on the cardiovascular system, in particular, is rooted in its involvement in vasodilation (activation of K ATP channels and the PI3K/Akt signaling pathway) [ 178 , 179 , 180 , 181 ], as well as its anti-inflammatory (inhibition of the p38 MAPK/NF-κB pathway) [ 182 , 183 ], antioxidative (activation of the Nrf2 signaling pathway) [ 59 , 168 , 184 ], and anti-apoptotic (suppression of pro-apoptotic genes Bid, Apaf-1, and p53) [ 140 ] properties, which have been extensively reviewed elsewhere in the literature [ 54 , 55 , 116 , 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent evidence has led to the attempt to affect the redox status of the myocardium to restore the necessary biochemical balance. For example, it has been shown that H2S therapy enhances phosphorylation and nuclear localization of nuclear factor erythroid 2-related factor 2 (NRF2), leading to the expression of NRF2-targeted downstream anti-oxidative stress genes, thus protecting cardiac tissue against I/R injury [37]. Moreover, antioxidants, free radical scavengers and traditional Chinese medicine can also protect against myocardial damage in ischemic heart disease [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2/ARE axis act as key signaling molecules in preventing oxidative damage of cardiac cell [ 153 ] and protects the heart against cardiac dysfunction and maladaptive remodeling [ 154 , 155 ]. Previous studies demonstrated that Nrf2 signaling is involved in the onset and progression of numerous heart disorders, including MI, myocarditis and atrial fibrillation [ 156 , 157 ]. Nrf2/HO-1 activation upregulates the transcription of several endogenous antioxidants and protects cardiomyocytes from damage caused by oxygen radicals [ 158 ].…”
Section: Cardiac Diseasesmentioning
confidence: 99%